Differential Toxicity of mDia Formin-Directed Functional Agonists and Antagonists in Developing Zebrafish - LeCorgne, Hunter; Tudosie, Andrew M.; Lavik, Kari; Su, Robin; Becker, Kathryn N.; Moore, Sara; Walia, Yashna; Wisner, Alexander; Koehler, Daniel; Alberts, Arthur S.; Williams, Frederick E.; Eisenmann, Kathryn M. (Frontiers in Pharmacology, 2018)
The mammalian Diaphanous-related (mDia) formins are cytoskeletal regulators that assemble and, in some cases, bundle filamentous actin (F-actin), as well as stabilize microtubules. The development of small molecule antagonists and agonists that interrogate mDia formin function has allowed us to investigate the roles of formins in disease states. A small molecule inhibitor of FH2 domain (SMIFH2) inhibits mDia-dependent actin dynamics and abrogates tumor cell migration and cell division in vitro and ex vivo tissue explants. mDia formin activation with small molecule intramimics IMM01/02 and mDia2-DAD peptides inhibited glioblastoma motility and invasion in vitro and ex vivo rat brain slices. However, SMIFH2, IMMs and mDia2 DAD efficacy in vivo remains largely unexplored and potential toxicity across a range of developmental phenotypes has not been thoroughly characterized. In this study, we performed an in vivo screen of early life-stage toxicity in Danio rerio zebrafish embryos two days post-fertilization (dpf) in response to SMIFH2, IMM01/02, and mDia2 DAD. SMIFH2 at concentrations ≥ 5-10μM induced significant defects in developing zebrafish, including shorter body lengths, tail curvature and defective tail cellularity, craniofacial malformations, pericardial edema, absent and/or compromised vasculature function and flow, depressed heart rates and increased mortality. Conversely, IMM and mDia2 DAD peptides were minimally toxic at concentrations up to 10-20μM and 50μM, respectively. SMIFH2’s therapeutic potential may therefore be limited by its substantial in vivo toxicity at functional concentrations. mDia formin agonism with IMMs and mDia2 DADs may therefore be a more effective and less toxic anti-invasive therapeutic approach.